A new beginning: can omidubicel emerge as the next, viable alternative donor source? - Arpita P. Gandhi; Laura F. Newell; Richard T. Maziarz (Therapeutic Advances in Hematology, 2023)
Umbilical cord blood (UCB) transplantation (CBT) has been an important alternative donor option for patients lacking matched related donor (MRD) or unrelated donor (URD) grafts. Only 30% of patients with high-risk hematologic malignancies have a human leukocyte antigen (HLA)-identical sibling; subjects without a MRD option are referred for HLA-matched URD selection, or utilize alternative donor sources such as HLA-mismatched URD, UCB, or haploidentical donor grafts. While CBT demonstrates an excellent graft- versus -leukemia (GVL) effect, use of UCB as a graft source is limited due to a lower cell dose that can result in delayed engraftment and an immature immune system with increased infectious risk as a consequence. Together, increased transplant related mortality (TRM) has been associated with UCB allografts. Omidubicel is an ex vivo expanded single cord blood product that has demonstrated rapid engraftment, improved immune reconstitution, and reduced infectious complications in clinical trials. Omidubicel has now been granted U.S. Food & Drug Administration approval to enhance neutrophil recovery and decrease infectious risk. This review will focus on CBT, benefits and barriers to using this alternative donor source, and finally the potential advancements with incorporation of omidubicel in the transplant setting for malignant and non-malignant diseases.